Analisis Persiapan Pelaksanaan Patient Safety di Ruang Rawat Inap; Study Kasus di RSUD Kabupaten Bima - Budiwibowo, Arif (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2018)
The era of globalization brings the very rapid effects in the development of cutting-edge medical technology. These conditions have an impact on medical services is very complex and very potentially cause errors, so that the necessary improvement of the quality of health services.  Patient safety is one important component in the quality of health services.  Improving patient safety measures needed to prevent and minimize unexpected events (KTD).  Nurses are one of the health workers who are at the front of health services have a very important role in improving patient safety. The aim of this research to assess patient safety analysis on the Attitudes of ward nurses in public district general hospital Bima and in particular to know the components of patient safety climate Attitudes include teamwork, job conditions, employment decisions, factors that support and hinder patient safety  Attitudes. The study was descriptive qualitative. Subjects were nurses of three subjects and patients with interviews.  Data collection techniques in this study are the tape recorder.  Qualitative data analysis technique that was using descriptive analysis techniques to describe the data in the field were analyzed and concluded. Attitudes of patient safety component of work climate Attitudes patient safety team showed low, job satisfaction shows high patient safety Attitudes at the components of job satisfaction, working conditions showed low Attitudes patient safety, because of logistical and laboratory support is still lacking. Components of patient safety high Attitudes namely job satisfaction component of patient safety is low Attitudes climate of teamwork and conditions of employment because of logistical   and laboratory support is still lacking.